Photo-physicochemical properties and in vitro photodynamic therapy activity of morpholine-substituted Zinc(II)-Phthalocyanines π-π stacked on biotinylated graphene quantum dots. (June 2019) - Nene, Lindokuhle C.; Managa, Muthumuni; Nyokong, Tebello
Abstract: Two morpholine-substituted Zn(II) phthalocyanines, complex 4 and the cationic 5, were synthesized and conjugated to graphene quantum dots (GQDs) and biotinylated GQDs (GQDs-biotin) by non-covalent π-π interactions. The GQDs-biotin are prepared as potential nanoparticle-based Pc delivery vector combined with a receptor-mediated transport system using biotin. The photo-physicochemical properties of the Pc complexes and their corresponding conjugates were studied. Upon conjugation, the fluorescence quantum yields decrease for 4 and 5, however, the triplet quantum yields were increased for the conjugates. All samples demonstrated singlet oxygen generation. For conjugated complexes, the singlet quantum yields decreased due to the screening effect in some cases. An increase in the photodynamic therapy activities upon quaternization was observed for the conjugates, with the cell viability decreasing from 66.2% to 51.2% after treatment for 4 -GQDs and 5 -GQDs, respectively. A relatively better performance was also observed for the cationic complex in combination with the biotin functionalized GQDs, 5 -GQDs-biotin, where the cell viability was 34.9% after treatment. Moreover, the cellular uptake of 5 -GQDs-biotin over 24 h was relatively higher compared to Pc complex alone and other Pcs-GQDs conjugates. Highlights: Morpholine-substituted Zn(II) phthalocyanines were conjugated to pristine and biotin graphene quantum dots (GQDs). Upon conjugation, the triplet quantum yields of the phthalocyanines increased. There was an increase in the photodynamic therapy activity of the cationic complexes when linked to biotin GQDs. Cellular uptake was higher for conjugates with biotin GQDs.